2008
DOI: 10.1111/j.1745-6606.2008.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self‐Regulation, Future Orientation, and Financial Knowledge in Long‐Term Financial Decisions

Abstract: This research examines potential explanations of why consumers have difficulty making personal financial decisions that will be most beneficial in the long run. Within the decision context of retirement savings, results from an experiment suggest that self-regulatory state, future orientation, and financial knowledge can influence consumer evaluations and intentions related to retirement investments (i.e., a 401(k) plan). Findings suggest that consumers who express higher levels of future orientation are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
185
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(211 citation statements)
references
References 24 publications
18
185
1
7
Order By: Relevance
“…The high level of self-regulation required to eat together regularly may strengthen the selfregulatory muscle thus providing the self-control necessary to save regularly and accumulate greater wealth across time. Greater self-regulatory resources also appeared to influence investment decisions in another study (Howlett, Kees, and Kemp, 2008). As previously mentioned, individuals in the current study who had greater self-regulation resources preferred diversifying their investments Hurst, Luoh, and Stafford (1998) found in their study that diversification of portfolio leads to greater wealth accumulation for households.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The high level of self-regulation required to eat together regularly may strengthen the selfregulatory muscle thus providing the self-control necessary to save regularly and accumulate greater wealth across time. Greater self-regulatory resources also appeared to influence investment decisions in another study (Howlett, Kees, and Kemp, 2008). As previously mentioned, individuals in the current study who had greater self-regulation resources preferred diversifying their investments Hurst, Luoh, and Stafford (1998) found in their study that diversification of portfolio leads to greater wealth accumulation for households.…”
Section: Discussionsupporting
confidence: 50%
“…Third, similar to a muscle that increases in strength and stamina through regular exercise, selfregulatory capacity increases when practiced and can be developed through conscious and routine use, thus exercise of self-regulation in one area can lead to greater self-regulation in seemingly unrelated areas. Howlett, Kees, and Kemp (2008) found that individuals' intentions to enroll in a 401(k) plan were lower when participants were in a depleted self-regulatory state resulting from a mentally intensive reading exercise. Furthermore, attitudes toward various investments were also affected by the depletion of self-regulatory resources.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Furthermore, it has been suggested that having many children should be negatively predictive of saving for old age (Galasso et al 2008), because children are themselves considered to be a source of support. Future time perspective has been shown to be positively related to retirement saving practices Howlett et al 2008;Jacobs-Lawson and Hershey 2005). Finally, as saving is typically the end result of financial planning, it would follow that those who generally enjoy planning (i.e., positive planning affect), might be more likely to save.…”
Section: Saving For Retirementmentioning
confidence: 99%
“…And, Bhandari and Deaves (2008) find that younger, more-educated, higher-earning advice-receiving males with a planner mindset hold more equity, and an understanding of asset allocation accentuates the impact of the key factors age, income and a planner mindset. Finally, Howlett, Kees and Kemp (2008) find that selfregulatory state, future orientation, and financial knowledge can influence consumer evaluations and intentions related to retirement fund investments. Findings suggest that consumers who express higher levels of future orientation are more likely to participate in a retirement plan, an effect moderated by self-regulatory state.…”
Section: Planning Constructsmentioning
confidence: 99%
“…Moreover, the field may benefit from future research designed to discriminate differential construct and predictive validity associated with constructs such as perceived planning importance as employed here, compared to other kindred constructs such as future time perspective (Jacobs-Lawson et al, 2004), future orientation (Howlett et al, 2008), propensity to plan (Deaves et al, 2007), and planner mindset (Bhandari & Deaves, 2008).…”
Section: Future Workmentioning
confidence: 99%